Allosteric Modulation of Chemoattractant Receptors - Allegretti, Marcello; Cesta, Maria Candida; Locati, Massimo (Frontiers in Immunology, 2016)
Chemoattractants control selective leukocyte homing via interactions with a dedicated family of related G protein-coupled receptor (GPCR). Emerging evidence indicates that the signaling activity of these receptors, as for other GPCR, is influenced by allosteric modulators, which interact with the receptor in a binding site distinct from the binding site of the agonist and modulate the receptor signaling activity in response to the orthosteric ligand. Allosteric modulators have a number of potential advantages over orthosteric agonists/antagonists as therapeutic agents and offer unprecedented opportunities to identify extremely selective drug leads. Here, we resume evidence of allosterism in the context of chemoattractant receptors, discussing in particular its functional impact on functional selectivity and probe/concentration dependence of orthosteric ligands activities.